Prognostic factors in inpatients with advanced cancer at a palliative care unit - Karla Santos da Costa Rosa; Amanda Soares Oliveira; Raphael de Paiva Cypriano; Livia Costa de Oliveira (Brazilian Journal of Oncology, 2022)
Objectives: This study aims to identify prognostic factors and their discriminatory ability in inpatients with advanced cancer at a palliative care unit (PCU). Material and Methods: Observational, prospective cohort study involving advanced cancer patients (October 2019 to May 2021) of their first admission to a PCU. Sociodemographic, clinical, functional, nutritional, and laboratory variables were evaluated. The outcome was death within 30 days. Kaplan-Meier curves, log-rank test, and Cox proportional hazard model were used to assess prognostic value. The C-statistic was used to test the predictive accuracy of the variables. Results: Among 136 patients, 77 (56.6%) died within 30 days and the median overall survival was 10 (interquartile range: 6-14) days. The variables of 30-day mortality were tumor in the gastrointestinal tract (GIT) (hazard ratio [HR]: 1.61, 95% confidence interval [CI]: 1.11-2.82), impaired functionality (HR: 1.73, 95%CI: 1.09-3.00), nutritional risk (HR: 4.58, 95%CI: 1.62-12.92), and albumin <3g/dL (HR: 1.88, 95%CI: 1.05-3.34). However, albumin presented acceptable discrimination, with a C-statistic value of 0.75. Conclusion: Inpatients with advanced cancer in the GIT, impaired functionality, reduced serum albumin, and at nutritional risk have a worse prognosis. Albumin concentration has better discriminatory ability than the other factors identified.